2021
DOI: 10.26434/chemrxiv-2021-3jdm1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anisotropic Foams Via Frontal Polymerization

Abstract: The properties of foams, an important class of cellular solids, are most sensitive to the volume fraction and openness of its elementary compartments; size, shape, orientation, and the interconnectedness of the cells are other important design attributes. Control of these morphological traits would allow the tailored fabrication of useful materials including highly porous solids, anisotropic heat conductors, tough composites, among others. While approaches like ice templating has produced foams with elongated … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Intriguingly, the oscillations in Tmax are reminiscent of patterns generated in the classical single-and multi-slit diffraction experiments; constructive and destructive interference of propagating waves provides a unique splitting pattern! Recently, Alzate-Sanchez and coworkers 152 demonstrated that well-defined pattern formation occurs in FROMP resins with high concentration of added solvent. In this system, FP is triggered at the base of the resin inside a test-tube; the heat of the reaction induces solvent boiling.…”
Section: Instability Driven Spontaneous Patterningmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, the oscillations in Tmax are reminiscent of patterns generated in the classical single-and multi-slit diffraction experiments; constructive and destructive interference of propagating waves provides a unique splitting pattern! Recently, Alzate-Sanchez and coworkers 152 demonstrated that well-defined pattern formation occurs in FROMP resins with high concentration of added solvent. In this system, FP is triggered at the base of the resin inside a test-tube; the heat of the reaction induces solvent boiling.…”
Section: Instability Driven Spontaneous Patterningmentioning
confidence: 99%
“…Apart from ATRP and polyurethanes, which have not been thoroughly investigated, only FROMP occurs catalytically with the use of the commercial Grubbs-type ruthenium alkylidene complexes (e.g., G1 and G2). 32,41,49,66,69,70,73,102,106,124,[145][146][147]151,152,160,162,163 Highly strained, cyclic olefins undergo living catalytic polymerization; frontally derived polymers of dicyclopentadiene (DCPD) exhibit desirable mechanical properties via extensive crosslinking during catalysis. Perhaps counterintuitively to most catalyst design principles, FROMP and polyurethane-based systems 68,72,[193][194][195] require worse catalysts to circumvent rapid background polymerization.…”
Section: Large-scale Fabrication and 3d-printingmentioning
confidence: 99%